BIBLIOMETRIC ANALYSIS OF RESEARCH TRENDS ON LEAN IN VIETNAM - Tôn Nguyễn Trọng Hiền (Tạp chí Khoa học Đại học Đà Lạt)
This paper develops a bibliometric, empirical study about Lean in Vietnam and globally to identify the state of the art and the agenda for future research in Vietnam related to Lean approach. The results show that there is still room for improvement regarding Lean leadership, lean innovation, and lean in the supply chain.